Development of a tier 3 method for calculating greenhouse gas emissions from pulp and paper mills in South Africa - Chikande, Adriano Quondie Persuade (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.